Pemberdayaan Kelompok Tani Desa Sumbersari dalam Pembuatan Pupuk Organik Cair (POC) sebagai Upaya Mewujudkan Green Economy - kasmiati, kasmiati; Taufik, Moh. Ilzam Nuzuli; Habibi, Baharudin Yusuf; Faida, Zukhrufa; Kusumaningtyas, Fathia; Al Ghifari, Lukman Aziz; Atisholikhah, Mar; Latifa, Auliya Nahrul; Cahyono, Jumanto Nur; Sari, Dewi Kurnia; Wahyuni, Budi; Sari, Nurul Aulia; Salamah, Sholihatus; Finzho, Oscar Leon Dera; Hasanah, Shafa’ Atul; Syahid, Rahmat; Hamidah, Akrimah (PPM LP2M UIN Alauddin Makassar, 2024)
This community empowerment is an effort to answer farmers' problems by minimizing the use of chemical fertilizers which contain elements that are harmful to soil fertility and how to create other alternatives for using environmentally friendly fertilizers. This empowerment method is carried out thematically based on village potential. Sumbersari Village, where most of the population works as farmers, has potential worthy of development in realizing community welfare while preserving existing agricultural land. The types of data in this empowerment consist of primary data and secondary data collected through three methods, observation, interviews, and documentation. The implementation of this empowerment includes 4 stages, preparation, production of Pupuk Organik Cair (POC), Socialization and Introduction to the general public, and evaluation. The result of this empowerment is that the people in Sumbersari Village have a good response in participating in a series of activities and are very enthusiastic about applying Pupuk Organik Cair (POC) because it is considered important for soil fertility and is more environmentally friendly. The author hopes that through this empowerment, the people of Sumbersari Village can increase the productivity of agricultural products while maintaining environmental sustainability. In addition, packaging also plays an important role in protecting product stability, extending shelf life, and ensuring safety during distribution.